Base-Promoted Carbocyclization Reactions of α-Substituted N-(2-Alkynylphenyl)acetamides - Chen, Yan-Jhu; Chuang, Che-Ping (Synthesis, 2016)
A synthetic method for highly functionalized quinolin-2(1H)-ones has been developed. The copper(II) chloride-catalyzed aerobic oxidative carbocyclization reactions of α-substituted N-[2-(phenylethynyl)phenyl]acetamides, via the Conia-ene-type intramolecular carbocupration onto the alkynyl moiety, produced 3,4-difunctionalized quinolin-2(1H)-ones. In the absence of copper(II) chloride, these α-substituted acetamides undergo base-promoted nucleophilic 6-exo-dig carbocyclization to generate 3-functionalized quinolin-2(1H)-ones. Several useful functional groups including benzoyl, alkanoyl, diethoxyphosporyl, cyano, and methoxycarbonyl groups are compatible with the reaction conditions. α-Substituted N-(2-ethynylphenyl)acetamides bearing a terminal C≡C bond could also be used to generate the corresponding 4-methyl-substituted quinolin-2(1H)-ones smoothly.
Keywords: copper salts; oxidative; carbocyclization; 2-alkynylarylamines; quinolin-2(1H)-ones